TIME MANAGEMENT PROBLEMS IN STUDENTS’ LIFE - Trigulova T.A.; Yunusova F.B. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Time management is a critical skill for students, affecting their academic performance, personal well-being, and ability to handle multiple responsibilities. Many students struggle to organize their time effectively, leading to procrastination, stress, and decreased productivity. This study explores the challenges students face in managing their time, the impact of poor time management on academic and personal life, and strategies that can improve time management skills. By examining the relationship between time management and academic procrastination, this research highlights the importance of planning, prioritization, and focus in achieving academic success. The findings suggest that developing strong time management habits not only enhances productivity but also reduces stress and promotes a balanced lifestyle, ultimately supporting both personal growth and academic achievement.